the Multicultural performing arts, crafts, festivals, and goods of Penang - Tan, Sooi Beng (Pusat Pengajian Seni, 2011)
As Penang port developed in the late eighteenth and nineteenth centuries, the trading of spices and the export of tin and rubber attracted settlers from the Malay Archipelago, Thailand, Burma, Hadhramaut, India, China and Europe. Penang was also an important stopover for pilgrims going to Mecca. The multiethnic nature of early Penang can be seen in the population census of Georgetown in 1835 which included Europeans, Armenians, Malays, Acehnese, Batak, Chinese, Chuliahs, Bengalese, Siamese, Burmese, Arabs, Parsees, Native Christians and Caffrees (Africans).